Simulation and optimization of methylammonium lead iodide (CH3NH3PbI3) perovskite solar cell - Song, Derui (Nanyang Technological University, 2020)
The world has been distressed by energy shortage and global warming for decades. Community of research have been studying on this issue under great pressure. Nowadays, a new type of solar cell which is made of the perovskite materials as the absorber has become the hottest photovoltaic (PV) device among researchers and scientists, due to it’s rapid growth of efficiency during the last 10 years, from 3.8% in 2009 [1] to more than 25% in 2020 [2]. No doubt, all the researchers and scientists around the world have been shocked by the performance of this “magical” material, and curious about how significant the change brought by it would be in a not too far future. To deeply understand the mechanisms of this type of PV devices, simulating the operation of the devices is indispensable. In practical design of solar cell devices, numerical simulators can provide theoretical feasibility predictions and optimizing the device structure before the physical manufactures, which can reduce both time and expense, and shorten the development circle to a very large extent at meantime. There are a variety of simulation programs currently used throughout the world among researchers and scientists, such as the AMPS, GPVDM, SILVACO, TCAD, MULTIPHYSICS, and SCAPS-1D. In this paper, a widely used simulator, the SCAPS -1D has been employed to simulate the perovskite solar cell structures. Thickness is an important parameter to all the layers of the device structure. This work simulated the impact of thicknesses of all the layers of a perovskite solar cell (PSC) to optimize the device structure. Two hole transferring materials (HTMs), the Spiro-OMeTAD and Cu2O, and two electron transferring materials (ETMs), the TiO2 and ZnO, have been employed in the PSCs. Four structures have been simulated and the optimized thicknesses are the absorber layer 600 nm, the HTM/ETM layer 200 nm, the FTO layer 100 nm. The best efficiency achieved is 17.92% with the Au/Cu2O /CH3NH3PbI3/ZnO structure. And the impact of the defect in ETM layer on the performance of PSC is also been briefly analysed that the defect is the main reason causing parameter variation along with the thickness of the ETM layer, for defect acts as the recombination centre.